2011
DOI: 10.1007/s13311-011-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Biosynthesis Inhibition Reduces Acute Seizures and Drug Resistant Chronic Epileptic Activity in Mice

Abstract: Summary: Experimental evidence and clinical observations indicate that brain inflammation is an important factor in epilepsy. In particular, induction of interleukin-converting enzyme (ICE)/caspase-1 and activation of interleukin (IL)-1β/ IL-1 receptor type 1 axis both occur in human epilepsy, and contribute to experimentally induced acute seizures. In this study, the anticonvulsant activity of VX-765 (a selective ICE/ caspase-1 inhibitor) was examined in a mouse model of chronic epilepsy with spontaneous recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
200
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 276 publications
(224 citation statements)
references
References 51 publications
23
200
0
1
Order By: Relevance
“…In our previous study in female FVB/N mice,10 we found that CBZ and PHT were not capable of suppressing paroxysmal EEG events, mostly HVSWs, which was consistent with previous studies on these drugs in the intrahippocampal kainate model 5, 6, 7. Instead, both CBZ and PHT increased HVSW frequency, indicating proconvulsant activity 10.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our previous study in female FVB/N mice,10 we found that CBZ and PHT were not capable of suppressing paroxysmal EEG events, mostly HVSWs, which was consistent with previous studies on these drugs in the intrahippocampal kainate model 5, 6, 7. Instead, both CBZ and PHT increased HVSW frequency, indicating proconvulsant activity 10.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, both CBZ and PHT increased HVSW frequency, indicating proconvulsant activity 10. However, by using stricter criteria for defining HVSWs (to distinguish them from interictal spikes), including an inter‐HVSW interval that was not clearly defined in previous studies,5, 6, 7, 10 we found that the effect of CBZ on epileptic EEG events strikingly changed so that FVB/N mice were not resistant anymore. Similarly, CBZ suppressed both HVSWs and HPDs in NMRI mice.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations